2017
DOI: 10.1016/j.triboint.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Local chemo-mechanical insights into the efficacy of ZDDP additives from in situ single asperity growth and mechanical testing

Abstract: This work combines nanoscale tribological wear methods, used to prepare zinc dialkyldithiophosphate (ZDDP) tribofilms under conditions of controlled loading, with site specific nanopillar compression testing to derive a relationship between the ZDDP growth conditions and resultant mechanical properties. The key finding is that ZDDP films grown at higher loads exhibit lower yield strengths, which correlate with differences in tribofilm chemistry. We hypothesize that the load sensitivity tribofilm properties may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Numerous studies have now shown that shear force can drive chemical reactions on surfaces; for example, film growth from reactions between zinc dithiophosphate and steel, [8,7,36,18] cleavage of oxygen and fluorine from graphene, [4] or dissociation of methyl thiolate from a copper surface [1]. These observations are consistent with a modification of the Arrhenius model in which a force applied along the reaction coordinate lowers the energy barrier for a reaction, thus accelerating chemical reactions.…”
Section: Introductionmentioning
confidence: 54%
“…Numerous studies have now shown that shear force can drive chemical reactions on surfaces; for example, film growth from reactions between zinc dithiophosphate and steel, [8,7,36,18] cleavage of oxygen and fluorine from graphene, [4] or dissociation of methyl thiolate from a copper surface [1]. These observations are consistent with a modification of the Arrhenius model in which a force applied along the reaction coordinate lowers the energy barrier for a reaction, thus accelerating chemical reactions.…”
Section: Introductionmentioning
confidence: 54%
“…Sometimes a gold film is used but either this is very thin and applied only to increase the yield of secondary electrons or to avoid sample charging [18,19], or the reason for the film and its thickness are not reported [20]. One notable exception is recent work by Liu et al [21] and Feng et al [22] who deposited thick Cr and Cu layers on ZDDP tribofilms, both to protect the latter during FIB and also to provide a sacrificial layer that could be flattened to enable nanopillar compression measurement.…”
Section: Damage To Zddp Films Using Fibmentioning
confidence: 99%